PENGARUH KOMPETENSI, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BAPENDA KOTA MAKASSAR - Ibnu Munzier Hasri Gani; Mashur Razak; Badaruddin Badaruddin (Nobel Management Review, 2021)
Lower realization than predetermined target values. One example of ineffective work management is the parking mechanism where most parking objects still use the manual system. This study aims to determine the effect of competence, work motivation and work discipline on the performance of employees of the Makassar City Regional Revenue Board either partially or simultaneously. This type of research is quantitative with a survey approach. This research was conducted at the Makassar City Regional Revenue Agency Office from September to October 2020. The population in this study was 139 with a sample of 73 people. The sample was obtained because all populations were sampled but only 73 respondents returned it and this number was deemed to have met the requirements based on the Slovin formula with a margin of error of 10 percent, totaling 58 people. Data collection techniques using questionnaires, observation, and review documentation. Existing data are processed using the SPSS application to carry out an impact test. The results showed that partially, competence has a positive and significant effect on employee performance. Work motivation has a positive but not significant effect on employee performance. Work discipline has a positive but not significant effect on employee performance. Simultaneously, employee competence, work motivation and work discipline have a positive and